THE DIFFERENCES OF HEMATOCRIT LEVEL IN IMMEDIATE AND DELAYED BLOOD SAMPLES ON MICROHEMATOCRIT METHOD - Dwijastuti, Ni Made Sri; Damarta, I Ketut Ari; Widiantari, Ni Putu (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background:Hematology specimen examination should be performed at room temperature in less than 2 hours. Recommended specimen storage temperatures are in the range of 2- 6C. However, examining laboratory samples with uncertain storage time and temperature is often delayed.Aims:To determine the difference between the hematocrit values of blood samples examined immediately and those that were delayed for more than 2 hours at room temperature.Methods:This study was conducted from April to June 2023 at the Clinical Chemistry Laboratory of Universitas Bali Internasional. A total of 24 venous blood samples were grouped into three treatment groups that were stored for 3 hours (P1), 6 hours (P2), and 12 hours (P3) at room temperature (18-220C), and one control group was examined immediately. Data were analyzed using the Mann-Whitney U test (?=0.05).The results:Statistical tests showed that the comparison of control with P1 was not significantly different (p=0.313), while the comparison of control with P2 (p=0.003) and the control with P3 (p=0.000) was significantly different.Conclusions:There was no significant difference in hematocrit values between blood samples examined immediately and blood samples delayed for 3 hours. Significant differences in hematocrit values were shown in comparing blood samples examined immediately with blood samples delayed for 6 hours and examined immediately with blood samples delayed for 12 hours.